Helping others by helping yourself? A perspective about corporate social responsibility, service quality and organizational reputation. - Pereira, B.; Duarte, A.P.; Neves, J. (XI Phd Meeting in Social and Organizational Psychology, 2015)
In a time where the competition in the business market is at its highest level, understanding the customers’ expectations and offer an excellence service, might be the needed factor of differentiation for achieving success. In this sense, service quality which is defined as a judgement on how much customers’ perceptions are in line with their previous service expectations, has a key role. Previous studies suggests that overcoming customers’ expectations translates into greater loyalty and higher purchase intentions. However, increasing the quality of service requires a solid organizational reputation. This in turn, makes almost essential to look at the constant pressures, namely by customers and workers, to an organization to engage in strategy management focused in corporate social responsibility, that is, conducting a transparent business and contributing to the sustainable development of the company and all the society in three different dimensions - social, economic and environmental. The literature suggests a straight relation between corporate social responsibility and service quality, but to the best of our knowledge it has never been empirically tested. In this context, we propose a new model of research where the perceptions of corporate social responsibility help to increase service quality, by boosting a positive organizational reputation. The proposed model was tested using data from a sample of 206 customers and 105 workers of a consultancy organization (online survey). Data are currently being analyzed which means that the final results will be ready to be presented at the meeting in May.